Five Rootstocks for “Emperor” Mandarin Under Subtropical Climate in Southern Brazil - Cruz, Maria Aparecida da; Neves, Carmen Silvia Vieira Janeiro; Carvalho, Deived Uilian de; Colombo, Ronan Carlos; Bai, Jinhe; Yada, Inês Fumiko Ubukata; Leite Junior, Rui Pereira; Tazima, Zuleide Hissano (Frontiers in Plant Science, 2021)
Rootstocks modulate several characteristics of citrus trees, including vegetative growth, fruit yield and quality, and resistance or tolerance to pests, diseases, soil drought, and salinity, among other factors. There is a shortage of scion and rootstock cultivars among the combinations planted in Brazil. “Ponkan” mandarin and “Murcott” tangor grafted on “Rangpur” lime comprise the majority of the commercial mandarin orchards in Brazil. This low genetic diversity of citrus orchards can favor pest and disease outbreaks. This study aimed to evaluate the agronomic performance, Huanglongbing (HLB) tolerance, and fruit quality of “Emperor” mandarin on five different rootstocks for nine cropping seasons under the subtropical soil-climate conditions of the North region of the state of Paraná, Brazil. The experimental design was a randomized block, with six replications, two trees per block, and five rootstocks, including “Rangpur” lime, “Cleopatra,” and “Sunki” mandarins, “Swingle” citrumelo, and “Fepagro C-13” citrange. The evaluations included tree growth, yield performance, fruit quality, and HLB disease incidence. “Emperor” mandarin trees grafted on “Rangpur” lime and “Swingle” citrumelo had early fruiting and high yield efficiency. “Rangpur” lime also induced the lowest tree growth, but low fruit quality. Trees on “Swingle” citrumelo and “Fepagro C-13” citrange showed low scion and rootstock affinity and produced fruits with high total soluble solids (TSS), with a lower number of seeds for those from trees on “Fepagro C-13” citrange. “Cleopatra” and “Sunki” mandarins induced higher juice content, while fruits from trees on “Cleopatra” also had higher TSS/titratable acidity (TA) ratio. “Emperor” mandarin trees were susceptible to HLB regardless of the rootstocks. Overall, “Cleopatra” and “Sunki” mandarins, “Swingle” citrumelo, and “Fepagro C-13” are more suitable rootstocks for “Emperor” mandarin under Brazilian subtropical conditions than “Rangpur” lime.